Implementation science as a leadership capability to improve patient outcomes and value in healthcare. Issue 6 (November 2019) - Votova, Kristine; Laberge, Anne-Marie; Grimshaw, Jeremy M.; Wilson, Brenda
When evidence thresholds are met, adopting healthcare innovations should add value, and this is forgone when evidence is not translated into practice. Activities that are not supported by evidence lead to ineffective or unnecessary care, or harm, poor outcomes, and low-value healthcare. This article provides an overview of implementation science, which is the scientific study of why implementation succeeds or fails. We draw parallels between the LEADS in a Caring Environment leadership framework and implementation science process models and frameworks. Taken together, the principles and practices in LEADS and the aims of implementation science are effectively quite similar and can be useful for healthcare management looking to optimize resources when implementing evidence-based practice and innovation into routine clinical care.